Measuring Malaysian lower secondary learners' reading ability on a CEFR-aligned text - Gopal, Revathi; Maniam, Mahendran; Nallaluthan, Kesavan (Universitas Syiah Kuala, 2023)
To capture learners interest in reading and help them understand the content of their reading, it is important to write at a level that aligns with their reading abilities. This will motivate learners to read and comprehend the material. A CEFR-aligned textbook is a valuable tool for improving the English language skills of lower secondary learners in English Language classrooms. Therefore, it is significant to assess learners reading competence in text comprehension using a reading text from a CEFR-aligned textbook. These assessments were conducted based on a narrative text from the CEFR-aligned textbook using two different techniques: miscue analysis and retelling. The sample comprised 20 C grade learners randomly selected from Malaysian lower secondary schools. The data on miscues were analysed quantitatively, following Goodman, Watson, and Burkes In-Depth Procedure (2005). The quality of retelling was evaluated based on the criteria set by Irwin and Mitchells (1983) 5-point scoring method. The findings revealed that all 20 learners achieved the target descriptor scale B1, indicating that they can read simple texts on topics relevant to their field and interests with sufficient comprehension. This study implies that CEFR-aligned reading texts are appropriate for lower secondary learners to read and understand. Furthermore, miscue analysis and retelling can effectively monitor learners reading comprehension levels and help enhance reading skills among low intermediate-level learners. Based on learners reading habits that require assistance, teachers can plan upcoming reading lessons.